2005
DOI: 10.1590/s0101-81752005000200029
|View full text |Cite
|
Sign up to set email alerts
|

Estagiamento de embriões de Macrobrachium olfersi (Wiegman) (Crustacea, Palaemonidae) através de critérios morfológicos nos dias embrionários

Abstract: Em embriões de Macrobrachium olfersi (Wiegman, 1836) foram analisadas as características morfológicas bem como o dia do desenvolvimento em que estas características surgiram. Machos e fêmeas de M. olfersi foram coletados na Ilha de Santa Catarina e colocados em aquários de água doce, na temperatura de 26°C e ciclo escuro e claro de 10:14 horas. Fêmeas ovígeras foram monitoradas diariamente para retirada de uma amostra de 20 ovos da câmara incubadora. O desenvolvimento embrionário foi caracterizado através do s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 22 publications
(20 reference statements)
4
4
0
Order By: Relevance
“…AbdB and abdA are genes involved in the formation of abdominal segments and are necessary for adequate standardization in the posterior region in P. hawaiensis (Martin et al, 2016;Serano et al, 2016). AbdB and abdA transcripts in M. olfersii embryos increased from E5 to E6 (8.1-and 21.5-fold, respectively; Figure 2i,j), which is in accordance with the growth and curvature of the caudal papilla (stage E6) for abdomen formation (Simões-Costa et al, 2005). These results suggest that Hox genes in M. olfersii are involved in the identity of the body segment, as occurs in other studied crustaceans (Abzhanov & Kaufman, 1999;Martin et al, 2016;Serano et al, 2016).…”
Section: Isoforms Ofsupporting
confidence: 64%
See 2 more Smart Citations
“…AbdB and abdA are genes involved in the formation of abdominal segments and are necessary for adequate standardization in the posterior region in P. hawaiensis (Martin et al, 2016;Serano et al, 2016). AbdB and abdA transcripts in M. olfersii embryos increased from E5 to E6 (8.1-and 21.5-fold, respectively; Figure 2i,j), which is in accordance with the growth and curvature of the caudal papilla (stage E6) for abdomen formation (Simões-Costa et al, 2005). These results suggest that Hox genes in M. olfersii are involved in the identity of the body segment, as occurs in other studied crustaceans (Abzhanov & Kaufman, 1999;Martin et al, 2016;Serano et al, 2016).…”
Section: Isoforms Ofsupporting
confidence: 64%
“…A similar temporal expression profile was observed in the Hox cluster genes of the decapod E. sinensis (Chinese mitten crab) from the gastrula stage to before the Zoea I stage (Cui et al, 2021). The formation of the head in M. olfersii starts at E4 before the formation of the posterior region of the embryo (Simões-Costa et al, 2005). Dfd, lab, pb, and Scr genes are expressed in specific segments in the head region of other crustaceans, as in P. scaber (Abzhanov & Kaufman, 1999) and P. hawaiensis (Serano et al, 2016).…”
Section: Isoforms Ofsupporting
confidence: 61%
See 1 more Smart Citation
“…This increase in the eye index of M. acanthurus corroborates findings reported for the crab Erimacrus isenbeckii (Brandt, 1848) (Nagao et al 1999) and for the lobster Homarus americanus Milne edwards, 1837, which showed an increase by 490 μm during incubation (Perkins 1972). An increase in the pigmentation percentage as development proceeds was already observed in palaemonids as M. olfersii (Müller et al 2003;Simões-Costa et al 2005), M. potiuna (Müller et al 2004), M. idella idella (Dinakaran et al 2013) and M. lamarrei (Rashid et al 2013) ( Table 1).…”
Section: Discussionmentioning
confidence: 70%
“…Thus, considering this brief panorama, the aim of this study was to investigate the effect of UVB radiation on embryonic cells of the freshwater prawn Macrobrachium olfersi, which are found in Southern Brazil, a region where high intensities of UV radiation are recorded. It is important to remark that during development, embryos stay for 14 days in the external ventral brood pouch of the ovigerous female . The pouch is open and this facilitates a constant revolving of the eggs toward the center and periphery of the egg mass, allowing all of them to be exposed to virtually equal UVB radiation.…”
Section: Introductionmentioning
confidence: 99%